War from Outer Space: Science Fiction or Emerging Reality? - Marsili, M. (The World Will Never be the Same! But, What New International Realities Will We Face?, 2021)
Space is governed by bilateral treaties that belong to the Cold War era. The withdrawal by the Trump Administration from two major treaties such as the Intermediate-range Nuclear Forces and Open Skies , blaming Russia for the decision, jeopardizes the space neutrality. U.S. President Biden took the decision to seek a five-year extension of New START, until Feb. 5, 2026, and Russia agreed. Nevertheless, the unilateral withdrawal from the Outer Space Treaty by one of the major space powers is likely. Space control is essential, given the heavy reliance on space systems and the rapidly increasing proliferation of missile technology and counterspace systems. Emerging disruptive technologies are game-changing and will determine the conflicts and the geopolitical scenario of next decades. Hypersonic weapons are changing the character of war, will play a huge role in the global power balance by undermining core pillars of geopolitics such as geography and technological power. Like a time machine, global defense and security concerns take us back to the time of the Strategic Defense Initiative - known as "Star Wars Program" - the satellites and space-based missile system established by the U.S. on the eve of the end of the Cold War, intended to protect the country from attack by Soviet ballistic strategic nuclear weapons. This missile shield programme was designed to render nuclear weapons obsolete, but it appears to have failed. Space has been elevated by the U.S. and NATO to warfighting domain and has already been militarized by Russia and raising China. So far, the international community failed to reach a solution to prevent an arms race in outer space. Space war is no more a science-fiction scenario; it’s an emerging reality. This presentation aims to shed light on the hazard of an outer space which is not governed by any rules and tackles the challenges coming from the militarization of this operational domain. The question is how to avoid a star war in Outer Space and to prevent a conflict on Earth from the above?